Capital structure and company performance: Did the COVID-19 pandemic matter? - Ganesh, Shivaal (College of Accounting, 2025)
PURPOSE The aim of this study is to measure the significance of the relationship between leverage and the financial performance of 137 non-financial companies from 2016 to 2023. This study also aims to draw comparisons between this relationship during the pre-COVID-19 Pandemic of 2016 to 2019, over the full period of 2016 to 2023, and post the start of the COVID-19 Pandemic, 2020 to 2023. METHODOLOGY A two-step least squares Generalised Method of Moments panel regression model using a forward orthogonal deviation to measure the significance of the relationship was utilised. This was accompanied by model robustness checks: Breusch-Godfrey Pagan, Lagrange-Multiplier, Durbin-Watson and Arellano and Bond Serial Correlation tests. FINDINGS This study identified multiple negative relationships that were statistically significant across the periods that were analysed. This includes total liabilities and return on equity (ROE) for the pre-COVID-19, COVID-19, and full periods. Non-current liabilities and ROE in the pandemic and full periods but not in the pre-pandemic periods. Current Liabilities and ROE for the pre-COVID-19 period and full period but were insignificant for the COVID-19 period. Total liabilities and return on assets (ROA) were found for the full period, but insignificant for the pre-COVID-19 and COVID-19 periods. Non current liabilities and ROA for the pre-COVID-19, COVID-19 and full periods. Current liabilities did not exhibit any statistically significant relationships with ROA for all three periods. From the findings of this study, we can conclude that companies should exercise caution when deciding to utilise leverage during crisis and non-crisis periods as it can harm financial performance. It therefore highlights the importance of financing strategies during periods of low economic activity. ORIGINALITY This study provides new evidence on the relationship between leverage and financial performance from a South African context. Additionally, it compares the relationships between the COVID-19 Pandemic and pre-COVID-19 periods, determining if the pandemic had any impact on the relationship. Three leverage variables are used: total, non-current- and current liabilities to evaluate the relationship of each type of leverage measure with financial performance.